Farm weeds of Gujarat: Exploiting the medicinal potential in Ayurveda - Solanki, R U; Chavda, N K; Thounaojam, A S; Chaudhary, R I; Patel, K V (Indian Horticulture, 2023)
In recent times, farmers of Gujarat have been accepting and exploiting organic ways to do the farming in all profitable ways possible. In this context, this article narrates the most efficient way to manage farm weeds without utilizing weedicides containing synthetic chemicals. By doing collection, processing and value-addition of the farm weeds, farmers can generate secondary source of income which will empower the small farmers to initiate small businesses using Ayurveda and also generate significant employment for the rural youth.